PERSEPSI WISATAWAN MANCANEGARA TERHADAP INTERNASIONALISASI LAYANAN RUMAH SAKIT DI MANADO PASKA PANDEMI: SEBUAH PENDEKATAN SERVICE MARKETING - Vincent Didiek Wiet Aryanto; Ivonne Angelic Umboh (Universitas Muhammadiyah Luwuk Banggai, 2022)
This study aims to determine the impact of the internationalization of several types A and B hospitals in the city of Manado and its surroundings. Manado was declared by the Ministry of Tourism as one of the main destinations in Indonesia. How to promote and bring in foreign tourists must be accompanied by security guarantees, the main ones being health insurance and access to international insurance when in tourist destinations. The research method was carried out by purposive convenient sampling carried out at the inns and hotels of the tourists staying. The results of the research stated that all foreign tourists have positive perceptions and beliefs about the existence and services of international hospitals in Manado, the thing that still makes them doubtful is about the completeness of international standard hospital facilities, but these doubts can be overcome with reassurance with evidence.